Exploring the Potential of Micrococcus luteus Culture Supernatant With Resuscitation-Promoting Factor for Enhancing the Culturability of Soil Bacteria - Lopez Marin, Marco Antonio; Strejcek, Michal; Junkova, Petra; Suman, Jachym; Santrucek, Jiri; Uhlik, Ondrej (Frontiers in Microbiology, 2021)
A bacterial species is best characterized after its isolation in a pure culture. This is an arduous endeavor for many soil microorganisms, but it can be simplified by several techniques for improving culturability: for example, by using growth-promoting factors. We investigated the potential of a Micrococcus luteus culture supernatant containing resuscitation-promoting factor (SRpf) to increase the number and diversity of cultured bacterial taxa from a nutrient-rich compost soil. Phosphate-buffered saline and inactivated SRpf were included as controls. After agitation with SRpf at 28 °C for one day, the soil suspension was diluted and plated on two different solid, oligotrophic media: tenfold diluted Reasoner’s 2A agar (R2A) and soil extract-based agar (SA). Colonies were collected from the plates to assess the differences in diversity between different treatments and cultivation media. The diversity on both R2A and SA was higher in the SRpf-amended extracts than the controls, but the differences on R2A were higher. Importantly, 51 potentially novel bacterial species were isolated on R2A and SA after SRpf treatment. Diversity in the soil extracts was also determined by high-throughput 16S rRNA amplicon sequencing, which showed an increase in the abundance of specific taxa before their successful cultivation. Conclusively, SRpf can effectively enhance the growth of soil bacterial species, including those hitherto uncultured.